Energy Drink Consumption: Beneficial and Adverse Health Effects - Alsunni, Ahmed Abdulrahman (International Journal of Health Sciences, 2015)
Consumption of energy drinks has been increasing dramatically in the last two decades, particularly amongst adolescents and young adults. Energy drinks are aggressively marketed with the claim that these products give an energy boost to improve physical and cognitive performance. However, studies supporting these claims are limited. In fact, several adverse health effects have been related to energy drink; this has raised the question of whether these beverages are safe. This review was carried out to identify and discuss the published articles that examined the beneficial and adverse health effects related to energy drink. It is concluded that although energy drink may have beneficial effects on physical performance, these products also have possible detrimental health consequences. Marketing of energy drinks should be limited or forbidden until independent research confirms their safety, particularly among adolescents. Disclosure of benefit: This work was not supported by any drug or commercial company.